Phthiriasis palpebrarum presenting as anterior blepharitis - Taskin Khan (Indian Journal of Public Health, 2018)
In humans, Pthirus pubis or crab louse usually infests hair of pubic region. Phthiriasis palpebrarum (infestation of the eyelashes and eyelids) is not as rare as is reported in literature, especially in low socioeconomic communities. It is possible that the disease is being perhaps missed due to its clinical similarity with anterior blepharitis. The nits and adult lice adhering to the eyelashes can easily be overlooked. This study presents five cases of phthiriasis palpebrarum, coming from the same locality and socioeconomic background, presenting with itching, hyperemia of lids, and excoriation of skin. Two patients were misdiagnosed elsewhere. All were successfully treated. The presence of P. pubis reflects the low level of health and hygiene of that stratum of the society. Higher prevalence could be related to rapid urbanization, overcrowding, and extreme poverty. The health-care providers and policymakers should give more merit to this not so uncommon disease having high morbidity.